Clinical, Bacteriological, and Histopathological Findings of a Testicular Fibrosis in a 6-Year-Old Lusitano Stallion. (29th September 2012) - Rocha, A.; Guimarães, T.; Duarte, J. C.; Cosinha, C.; Lopes, V. T. A.; Faria, F.; Amorim, I.; Gärtner, F.
Abstract : A 6-year-old Lusitano stallion was referred to our centre due to an enlarged left testicle. Anamnesis indicated that the stallion had a chronic hypertrophy of the left testicle, with no apparent ill effect on work (dressage training) or semen production. Prolonged use of anti-inflammatory drugs (NSAIDs) and antibiotics were probable. Upon examination of the animal, it was found that clinical signs were compatible with chronic testicular degeneration or fibrosis. Ultrasound scanning did not evidence the exuberant macroscopic lesions seen upon hemicastration of the left testicle, but it showed in the left spermatic cord a conspicuous absence of the typical hypoechogenic areas representing the pampiniform plexus. Swabbing of the penis, prepuce, and distal urethra resulted in the isolation of Rhodococcus equi and Corynebacterium spp. However, histopathological examination did not support infectious orchitis as cause of the lesions and no bacterial growth was obtained from swabbing of the parenchyma in the excised testicle. Histopathological findings were compatible with chronic orchitis with fibrosis and necrosis, probably secondary to ischemia of the testicular parenchyma. After hemi-castration, the stallion resumed semen production at acceptable levels.